Potential Role of Ayurveda in the Management of Maple Syrup Urine Disease (AYUSHDHARA, 2025)
Maple syrup urine disease (MSUD) is a genetically inherited metabolic condition that follows an autosomal recessive pattern. It results from malfunction in the branched-chain alpha-ketoacid dehydrogenase (BCKAD) complex, essential for the breakdown of branched-chain amino acids (BCAAs) such as leucine, isoleucine and valine. A defective BCKAD complex impairs the normal degradation of BCCAs, leading to their accumulation. This condition is marked by neurological and developmental issues, feeding difficulties, a distinctive maple syrup smell in the urine, including encephalopathy. Elevated blood levels of BCAAs and increased urinary excretion of their corresponding ketoacids are hallmark feature. When treatment begins early, individuals often experience positive clinical outcomes. Material and Methods- In this case, a 22-year-old male patient who a known case of hypertension, was brought by his parents with concerns of recurrent seizures occurring two to three times per week for the past 8 years, global developmental delay noted since infancy along with recurrent upper respiratory tract infections, salivary dribbling, excessive eating habit, irritable behaviour– since childhood. Associated with reduced sleep since childhood and masturbatory behaviour since 15 years of age. Patient was treated with Shamanaushadhi as a part of the management protocol. Results- This intervention led to substantial improvement in multiple aspects of the patient’s clinical presentation. Conclusion- The case indicates potential benefits of Ayurveda treatment in improving clinical outcomes and quality of life in an MSUD patient.